2015
DOI: 10.1016/j.jbusres.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic view on secrecy management

Abstract: a b s t r a c t Available online xxxxKeywords: Secrecy Innovation Appropriability Secrecy management lifecycle Purpose -The current study provides a literature review on secrecy as mechanism for appropriating value from innovation. It synthesizes previous findings into a framework that can explain the advantages of exercising secrecy versus patenting. It also examines the management lifecycle of secrecy. Design/methodology/approach -It takes a dynamic perspective and suggests a four-stage secrecy management li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Moreover, we found that increases in the proactive orientation of SMEs weakens the relationship between family SMEs compared to non-family SMEs and their preferences for patenting relative to secrecy. Our findings therefore suggest that firm-level characteristics significantly contribute to our understanding of when SMEs use patents rather than secrecy, expanding the organisational factors identified by Bos et al (2015) in the IP literature.…”
Section: Contributions To Theorysupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, we found that increases in the proactive orientation of SMEs weakens the relationship between family SMEs compared to non-family SMEs and their preferences for patenting relative to secrecy. Our findings therefore suggest that firm-level characteristics significantly contribute to our understanding of when SMEs use patents rather than secrecy, expanding the organisational factors identified by Bos et al (2015) in the IP literature.…”
Section: Contributions To Theorysupporting
confidence: 54%
“…Recent innovation research suggests that innovative products and practices are expected to be safeguarded through different strategies and mechanisms (Bos et al, 2015), including secrecy and patenting. Patenting and secrecy are considered strategies that proactive firms use to protect their knowledge (Sofka et al, 2018;Veugelers and Schneider, 2018).…”
Section: The Choice Between Secrecy and Patentingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also some evidence that firms deliberately disclose certain knowledge to the general public ("selective revealing") in order to spur complementary innovations (Alexy, George, and Ammon 2013;Henkel, Sch€ oberl, and Alexy 2014). In addition, the strategic use of secrecy has been supported by the emergence of thorough secrecy management in firms (Bos, Broekhuizen, and de Faria 2015).…”
Section: Open Innovation Practicesmentioning
confidence: 99%
“…Secrecy is a widely used and efficient knowledge protection mechanism in virtually all industries and firms of all types and sizes (Bos et al, 2015;Hall, Helmers, Rogers and Sena, 2014;Harabi, 1995;James, Leiblein and Lu, 2013). Firms actively restrict information flows both within and outside their boundaries with the objective of limiting unintended information spillovers (James et al, 2013).…”
Section: Introductionmentioning
confidence: 99%